Intensive care unit providers more quickly and accurately assess risk of multiple harms using an engineered safety display. (December 2019) - Romig, Mark; Carolan, Howard; Ravitz, Alan; Schell-Chaple, Hildy; Yoon, Edward; Dwyer, Cindy; Thornton, Kevin; Gropper, Michael; Pronovost, Peter J; Sapirstein, Adam
Project Emerge took a systems engineering approach to reduce avoidable harm in the intensive care unit. We developed a socio-technology solution to aggregate and display information relevant to preventable patient harm. We compared providers' efficiency and ability to assess and assimilate data associated with patient-safety practice compliance using the existing electronic health record to Emerge, and evaluated for speed, accuracy, and the number of mouse clicks required. When compared to the standard electronic health record, clinicians were faster (529 ± 210 s vs 1132 ± 344 s), required fewer mouse clicks (42.3 ± 15.3 vs 101.3 ± 33.9), and were more accurate (24.8 ± 2.7 of 28 correct vs 21.2 ± 2.9 of 28 correct) when using Emerge. All results were statistically significant at a p -value < 0.05 using Wilcoxon signed-rank test ( n = 18). Emerge has the potential to make clinicians more productive and patients safer by reducing the time and errors when obtaining information to reduce preventable harm.